2020
DOI: 10.3389/fneur.2020.00881
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Mechanisms of LRRK2 G2019S Penetrance

Abstract: Several mutations in leucine-rich repeat kinase-2 (LRRK2) have been associated with Parkinson's disease (PD). The most common substitution, G2019S, interferes with LRRK2 kinase activity, which is regulated by autophosphorylation. Yet, the penetrance of this gain-of-function mutation is incomplete, and thus far, few factors have been correlated with disease status in carriers. This includes (i) LRRK2 autophosphorylation in urinary exosomes, (ii) serum levels of the antioxidant urate, and (iii) abundance of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Although we failed to detect an effect of LRRK2 inhibition of global cellular mitochondrial respiration, it is possible a small pool of mitochondria has altered oxygen consumption that impacts mitophagy. Indeed, deleterious mitochondrial phenotypes have been observed in LRRK2 G2019S patient-derived cells ( Delcambre et al, 2020 ; Mortiboys et al, 2010 ; Sanders et al, 2014 ), although further work is needed to clarify if this is a cause or consequence of impaired mitophagy. It is important to note that GSK3357679A led to activation of mitochondrial biogenesis via PGC-1β and not PGC-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Although we failed to detect an effect of LRRK2 inhibition of global cellular mitochondrial respiration, it is possible a small pool of mitochondria has altered oxygen consumption that impacts mitophagy. Indeed, deleterious mitochondrial phenotypes have been observed in LRRK2 G2019S patient-derived cells ( Delcambre et al, 2020 ; Mortiboys et al, 2010 ; Sanders et al, 2014 ), although further work is needed to clarify if this is a cause or consequence of impaired mitophagy. It is important to note that GSK3357679A led to activation of mitochondrial biogenesis via PGC-1β and not PGC-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Coding variants in LRRK2 leading to PD segregate to its catalytic core, such as in the GTPase domain (R1441C/G/H or Y1699C) and in its kinase domain (G2019S and I2020T). The G2019S mutation being the most frequent genetic cause of PD, representing 4–5% of familial cases and about 1% of sporadic cases [ 88 ]. All the known pathogenic mutations of LRRK2 lead to an increased kinase activity [ 89 ].…”
Section: Lrrk2 and Basal Mitophagymentioning
confidence: 99%
“…Work has shown that patient-derived fibroblasts from G2019S carriers display abnormal mitochondrial morphology and function [ 92 ]. Likewise, this same LRRK2 mutation has been shown to increase mitochondrial DNA damage in human-derived cells [ 88 , 93 ]. The abnormal mitochondrial phenotype is also present in mice with aged G2019S knock-in animals displaying hallmarks of impaired fission and altered dynamics [ 94 , 95 ].…”
Section: Lrrk2 and Basal Mitophagymentioning
confidence: 99%
“…For example, at the age of 60 years, 60% of Tunisian p.G2019S pathogenic variant carriers manifest PD, compared with only 20% of the Norwegian carriers of the same pathogenic variant ( 4 ). Recent studies have suggested mitochondrial involvement in the penetrance of LRRK2 -linked PD ( 5 , 6 ). Environmental factors can also influence penetrance, as recently found in the Tunisian Arab Berber population, where tobacco and black tea use delayed age at onset in LRRK2 pathogenic variant carriers ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently published data from the currently largest multinational prospective study that includes LRRK2 pathogenic variant carriers, i.e., the Parkinson's Progression Markers Initiative (PPMI), provide more phenotypic details on LRRK2 pathogenic variant carriers across international sites ( 6 ). However, as the focus of the PPMI study is predominantly on biomarkers, it does not cover environmental factors in-depth, and only includes participants with a PD diagnosis 2 years or less before enrolment who are untreated with PD medication.…”
Section: Introductionmentioning
confidence: 99%